A NOTE ON THE DOL-NET FISHERY OFF JAFFRABAD (GUJARAT) WITH SPECIAL REFERENCE TO BOMBAYDUCK, FROM 1979-80 TO 1981-82 - Khan, Mohammad Zafar (Indian Journal of Fisheries, 2011)
An estimated catch of 17,345.6 t were landed at JafTrabad by dol nets. The bombayduck formed about 90.6% of the landings. The peak periods of abundance were October-November (CPUE 245.0 and 216.9 kg) and May (CPUE 231.4 kg). The size range of bombayduck varied between 30 mm and 375 mm. Juveniles below 210 mm were more abundant during February-May (93 7 to 98.6%). The bycatch consisted of Coilia dussumeiri (2.6%), non-penaeid prawns (2.2%), penaeid prawns (0.8%), Ghol (1.7%) and Trichiums (0.7%). Considerable quantities of Pampns argenteiis (25.3 tonnes) in the size range 30 to 149 mm were also landed